1986
DOI: 10.1017/s0308229600015142
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dose and method of administration of recombinant bovine somatotropin on fleece growth and body composition in young, fattening lambs

Abstract: Daily injections of bovine pituitary somatotropin (growth hormone) can markedly increase growth and muscle deposition in fattening lambs, although the optimal dose range for these effects is not known.This experiment was designed to assess the anabolic and lipolytic activities of biosynthetic somatotropin (produced by genetically-modified bacteria) in fattening lambs, and to determine the effects of dose and method of administration.Dorset Down x Finn-Dorset lambs were individually penned, fed a barley/soyabea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Pelvic and internal fat tissue did not change in bST group. This finding is in agreement with previous studies (McLaughlin et al 1994;Godfredson et al 1990;Johnsson et al 1986;Muir et al 1983). Analysis of the carcasses showed some carcass components were affected by bST treatment.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Pelvic and internal fat tissue did not change in bST group. This finding is in agreement with previous studies (McLaughlin et al 1994;Godfredson et al 1990;Johnsson et al 1986;Muir et al 1983). Analysis of the carcasses showed some carcass components were affected by bST treatment.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have reported that somatotropin treatment had little effect on growth, feed intake and feed conversion of lambs (Johnsson et al 1986). Similarly, ovine growth hormone (oGH) and recombinant bovine somatotropin did not alter average daily live weight gain and feed intake (Muir et al 1983;Bird et al 1996).…”
Section: Discussionmentioning
confidence: 93%
“…Preliminary results have been published previously in abstract form (Johnsson, Butler-Hogg, Hathorn and Wilde, 1986). Preliminary results have been published previously in abstract form (Johnsson, Butler-Hogg, Hathorn and Wilde, 1986).…”
Section: Introductionmentioning
confidence: 99%